Caracterização das estruturas metálicas: um estudo de caso em Natal, Mossoró, Pau dos Ferros, São Francisco do Oeste e Portalegre no RN - Sousa Neto, Pedro Alves de (Universidade Federal Rural do Semi-Árido, 2019)
The use of steel has emerged as one of the alternatives to change the landscape of the construction sector, due to its advantages, such as: freedom in architectural design, larger useful area, flexibility, shorter execution time, among others. Even though it is gradually evolving late, national consumption is still below the level of countries with compatible level of development. Based on this, this work aims to conduct a survey and characterization of the number of civil engineers in the municipality of Pau dos Ferros, as well as the manufacturers and suppliers of steel structures in the state of Rio Grande do Norte. After analyzing the data obtained, it was noticed that, among the interviewees, steel ASTM A36 and ASTM A572 as well as type I and U profiles are the most commercialized by suppliers and used by manufacturers, where they do not have technical qualifications, mostly. Regarding civil engineers, although they all claim to know the advantages of metal structures, they claim that the frequency of concrete works is higher, a fact caused mainly by regional, cultural and unviable logistics factors.
Keywords: Fornecedores; Aço; Perfis estruturais; Construção civil; Providers; Steel; Structural profiles; Construction; ENGENHARIAS::ENGENHARIA CIVIL